1985
DOI: 10.1093/oxfordjournals.eurheartj.a061777
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pacemaker dependent patients by serial decremental rate inhibition

Abstract: In a study of the concept of pacemaker dependence, 86 patients who had permanent ventricular demand (VVI) pacemakers implanted for more than six months and were in predominantly paced rhythm underwent repeated interruption of pacing both abruptly and after gradual reduction of paced rate. Non-invasive pace slowing was accomplished by timed inhibiting pulses applied to the chest wall. The results identified a small group (A) of patients, 8% of those tested, who consistently failed to develop an adequate escape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The detection method of pacemaker dependency in the pacemaker clinic is also important. Compared with the sudden cessation of pacing, a gradual slowing of the pacing rate used in the present study allows the more consistent emergence of an escape rhythm in highly pacemaker dependent patients, 3 therefore, it is safer and better tolerated by patients. Backup temporary pacing at a rate of 30 beats/min for the evaluation of pacemaker dependency is also reliable, since patients who have a stable infranodal escape rhythm are reported to be unaffected by overdrive pacing at a rate of ≤50 beats/min 8 , 10 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The detection method of pacemaker dependency in the pacemaker clinic is also important. Compared with the sudden cessation of pacing, a gradual slowing of the pacing rate used in the present study allows the more consistent emergence of an escape rhythm in highly pacemaker dependent patients, 3 therefore, it is safer and better tolerated by patients. Backup temporary pacing at a rate of 30 beats/min for the evaluation of pacemaker dependency is also reliable, since patients who have a stable infranodal escape rhythm are reported to be unaffected by overdrive pacing at a rate of ≤50 beats/min 8 , 10 …”
Section: Discussionmentioning
confidence: 97%
“…Permanent pacemaker recipients who have no intrinsic or escape rhythm may develop complications under conditions of electromagnetic interference, lead dysfunction, or battery depletion. Few studies have examined the incidence of pacemaker dependency after device implantation 1‐3 . A recent report from the Canadian Trial of Physiologic Pacing (CTOPP) Investigators indicated that pacemaker dependency, defined as an intrinsic heart rate ≤60 beats/min, has an important influence on cardiovascular and total mortality, as does the selection of pacing mode 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all of its importance to clinical research 5,6 and recall there are limited published studies on how bradycardia dependency should be measured or on the stability of the measurements 7 . Why, for example, should one consider only the extreme of 30 beats/min as dependence?…”
mentioning
confidence: 99%
“…For all of its importance to clinical research 5,6 and recall there are limited published studies on how bradycardia dependency should be measured or on the stability of the measurements. 7 Why, for example, should one consider only the extreme of 30 beats/min as dependence? Many active elderly patients may have a significant clinical sequel to a sudden switch to 40 beats/min or to even faster escape rates.…”
mentioning
confidence: 99%